Formation Features of Hybrid Magnetic Materials Based on Polyphenoxazine and Magnetite Nanoparticles - Ozkan, S.Zh.; Karpacheva, G.P.; Dzidziguri, E.L.; Chernavskii, P.A.; Bondarenko, G.N.; Pankina, G.V. (Journal of Research Updates in Polymer Science, 2016)
Hybrid metal-polymer nanocomposite materials based on polyphenoxazine (PPhOA) and Fe3O4 nanoparticles were obtained for the first time via two methods: in situ oxidative polymerization of phenoxazine (PhOA) in an aqueous solution of isopropyl alcohol with nanoparticles of Fe3O4 being present; chemical transformations of PPhOA subjected to IR heating at 400–450 °С in the presence of FeCl3·6H2O in an inert atmosphere. Obtained hybrid Fe3O4/PPhOA nanomaterials were characterized by means of Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD), transmission electron microscopy (TEM), atomic absorption spectrometry (ААS), elemental analysis, differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), as well as by vibrating sample magnetometry. The chemical structure, phase composition, magnetic and thermal properties of obtained nanocomposites were investigated in relation to the synthesis conditions.